Untreated Patients Dying With AIDS Have Loss of Neocortical Neurons and Glia Cells - Kaalund, Sanne Simone; Johansen, Annette; Fabricius, Katrine; Pakkenberg, Bente (Frontiers in Neuroscience, 2020)
Human immunodeficiency virus (HIV) infects immune cells in the blood and brain and, if left untreated, leads to acquired immunodeficiency syndrome (AIDS). HIV infects the immune cells of the brain, microglia and astrocytes, but not oligodendrocytes and neurons. However, it is the loss of axons and white matter damage that are thought to cause the cognitive symptoms associated with HIV and AIDS. We used design-based stereology to investigate the numbers of neocortical neurons and glial cells, divided into astrocytes, oligodendrocytes and microglia, in patients dying with AIDS. Our study included 12 AIDS patients and 13 controls, all males between 20 and 67 years of age. We report a significant 19% loss of neocortical neurons (p=0.04) and a 29% reduction in the number of oligodendrocytes (p=0.003) in patients with AIDS. There were no significant differences in the numbers of astrocytes and microglia between patients and controls. Furthermore, we observed a significant reduction of 17% in hemispheric volume in patients with AIDS (p = 0.0015), both the neocortical and white matter volumes were reduced (p <0.05), while the volumes of archicortex, subcortical grey matter and ventricles were within normal limits. Our results confirm previous reports of neuronal loss in AIDS. The selective loss of oligodendrocytes in treatment-naïve patients is in agreement with the notion that HIV-1 in the brain is associated with demyelination and axonal dysfunction and suggests that remyelination treatment strategies may be beneficial to patients suffering from HIV associated neurocognitive disorder.